2010
DOI: 10.1021/jf904493f
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Guided Fractionation to Characterize a Coffee Beverage that Effectively Down-Regulates Mechanisms of Gastric Acid Secretion as Compared to Regular Coffee

Abstract: In some individuals, the consumption of coffee beverages is related to symptoms of gastric irritation. Hot water steam-treatment of raw coffee beans is hypothesized to reduce the contents of stomach irritating compounds, and products to which this technology is applied are launched as stomach-friendly coffee. However, data on the effect of steam-treated coffee on gastric acid secretion are conflicting and it has not been proven yet as to which coffee components act as pro- or antisecretory stimulants. The work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…N-MP also down-regulated the mRNA expression of the pro-secretory CHRM3. This finding is in accordance with the anti-secretory effect of N-MP after its addition to a lyophilized coffee beverage [9] and is also supported by an anti-ulcerogenic effect described in rats for 1-methylnicotinamide, a structure closely related to N-MP [18]. Thus, substituted pyridine structures may exhibit a stomach protective potential.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…N-MP also down-regulated the mRNA expression of the pro-secretory CHRM3. This finding is in accordance with the anti-secretory effect of N-MP after its addition to a lyophilized coffee beverage [9] and is also supported by an anti-ulcerogenic effect described in rats for 1-methylnicotinamide, a structure closely related to N-MP [18]. Thus, substituted pyridine structures may exhibit a stomach protective potential.…”
Section: Discussionsupporting
confidence: 86%
“…For the activation of the transcription factor ATF‐2, N‐MP, CAT and C5HT increased its phosphorylation status, whereas CAFF did not. In previous studies, it has already been shown that lyophilized coffee beverages with higher contents of N‐MP increase ERK1/2 activation compared with controls, whereas lyophilisates of coffee beverages with lower contents of N‐MP decreased the activity below control levels .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although these results do not provide conclusive evidence that the ratio of N‐MP to C5HTs and CGAs is predicative for the gastric acid stimulating potential of a coffee beverage, we further hypothesize that high concentrations of N‐MP in combinations with low concentrations of C5HTs and CGAs might be beneficial for subjects who react to coffee consumption with increased gastric acid secretion. From a mechanistic point of view, this hypothesis is supported by previous studies in which N‐MP was identified as an antisecretory constituent . Moreover, N ‐methylnicotinamide, another pyridine derivative, was shown to exhibit an anti‐ulcerogenic potential .…”
supporting
confidence: 71%
“…This shows that coffee may potentially have some benefit in the treatment of PD. Another study concluded that N-methylpyridinium infused coffee limited proton secretion in human gastric cells in a dose dependent fashion (Rubach et al, 2010). This research shows the power of coffee and Nmethylpyridinium to influence gene expression and downregulate gastric acid secretion.…”
Section: Introductionmentioning
confidence: 69%